2000
DOI: 10.1238/physica.regular.061a00222
|View full text |Cite
|
Sign up to set email alerts
|

Element Abundances in the Upper Atmospheres of the Sun and Stars: Update of Observational Results

Abstract: We review observational progress in the determination of element abundances in the solar corona, largely due to the new capabilities offered by the instrumentation on the SOHO satellite. Many new facets to coronal abundance anomalies with respect to the photosphere are revealed. This includes new results on the FIP (First Ionization Potential) Effect, whereby elements with FIP < 10 eV are enriched in the corona by a factor ~4 with respect to the photosphere, and the first evidence for gravitational settling of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
186
3

Year Published

2005
2005
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 188 publications
(206 citation statements)
references
References 145 publications
17
186
3
Order By: Relevance
“…We note, however, that such abundance variations might not be unreasonable in the light of a recent survey of coronal densities by Testa et al (2004) that clearly demonstrates that the cooler T $ 10 6 K corona resides in quite different structures to the hotter, T $ 10 7 K plasma that appears to be universally characterized by much higher pressures. Feldman & Laming (2000) found that for the solar corona the FIP effect is larger at T $ 10 5:9 K than at T $ 10 6:15 K.…”
Section: Temperature Structurementioning
confidence: 90%
See 1 more Smart Citation
“…We note, however, that such abundance variations might not be unreasonable in the light of a recent survey of coronal densities by Testa et al (2004) that clearly demonstrates that the cooler T $ 10 6 K corona resides in quite different structures to the hotter, T $ 10 7 K plasma that appears to be universally characterized by much higher pressures. Feldman & Laming (2000) found that for the solar corona the FIP effect is larger at T $ 10 5:9 K than at T $ 10 6:15 K.…”
Section: Temperature Structurementioning
confidence: 90%
“…The resulting ratio of measured line fluxes then yields directly the ratio of the abundances of the relevant elements, independently of the atmospheric temperature structure. A similar, although less sophisticated, method has been previously used in solar coronal observations (see, e.g., Feldman 1992;Feldman & Laming 2000) and in stellar EUVE observations (Drake et al , 1997.…”
Section: Element Abundancesmentioning
confidence: 99%
“…However, from shortly after and for the duration of the observations the abundance ratio continued to change until it reached a factor of ≈9 after five to six days. For review papers describing the recent findings that relate to the composition of the solar atmosphere see Feldman (1992), Saba (1995), Fludra et al (1999b), Feldman and Laming (2000), and Feldman and Widing (2003). Ko et al (2006) used in situ data from the Solar Wind Ion Composition Spectrometer (SWICS) on board the Advanced Composition Explorer (ACE) spacecraft at ≈1 ua in combination with spectroscopic data from UVCS measured at 1.64 R to investigate the coronal origin of the solar wind.…”
Section: Composition Of the Coronamentioning
confidence: 99%
“…Solar abundances have been derived both from optical/UV/X-ray spectroscopy and from composition measurements of solar wind particles or meteorites (Feldman & Laming 2000), but the most recent and sophisticated results are in stark conflict with models of the solar interior tuned with helioseismology data (Asplund et al 2009). A second problematic point is the finding that photospheres of stars hosting close-in giant planets are known to be metal-rich, which can possibly be explained by a higher probability of planet formation in highmetallicity birth clouds (Gonzalez 2006).…”
Section: Introductionmentioning
confidence: 99%
“…In this respect, stellar X-ray spectroscopy is a fundamental tool for the chemical analysis of stellar outer atmospheres, and the only method to determine the abundances of noble gases, like argon and neon, with no optical lines in photospheric spectra. For the solar corona, and in particular in long-lived coronal structures, the composition of the plasma appears enriched with elements having low first ionization potentials (FIP < 10 eV) by about a factor 4, on average, with respect to photospheric values (Feldman & Laming 2000). In other stars a more complex behavior has been observed (Güdel & Nazé 2009), with a tendency for the low-FIP elements (including iron) to become depleted with respect to the high-FIP elements (neon in particular) in extremely active RS CVn-type and Algol-type binaries.…”
Section: Introductionmentioning
confidence: 99%